2012
DOI: 10.1002/ccd.24656
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery fistula with a giant aneurysm treated by percutaneous transradial embolization

Abstract: Coronary artery fistulas are rare anomalies that are very rarely accompanied by an aneurysm. The minimally invasive method of percutaneous transradial embolization, using a thin guiding catheter, was used to treat a coronary artery fistula with an associated giant aneurysm. This technique, not previously described for this type of application, is presented as a case report. The successful outcome of this procedure demonstrated that transradial coronary interventions are useful for treating coronary artery fist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Percutaneous transfemoral and transradial approaches for embolization of a fistula have been reported. In our patients, PTE via the transfemoral approach was performed in 4 patients; in 1 of those, failure of PTE occurred due to fistulous vessel tortuosity and lack of guiding catheter support.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transfemoral and transradial approaches for embolization of a fistula have been reported. In our patients, PTE via the transfemoral approach was performed in 4 patients; in 1 of those, failure of PTE occurred due to fistulous vessel tortuosity and lack of guiding catheter support.…”
Section: Discussionmentioning
confidence: 99%
“…The size is specified as follows: small, <1× distal reference; medium, 1 to 2× distal reference; and large, >2× distal reference ( 5 ). Several studies reported that indications for closure are high Q p /Q s (1.3 to 1.5), the presence of large fistulas, ECG-indicated myocardial ischemia, PA hypertension progression, congestive heart failure, and/or coronary aneurysm with a high risk of rupture ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, TAE is less invasive than surgery and is now widely performed, although the early effectiveness, morbidity, and mortality for both approaches have been reported to be similar [6] . Recently, elective TAE for CAFs with unruptured aneurysms has also been reported [9] , [10] . Iwasawa et al reported a case of CAF with a ruptured aneurysm, which was treated by TAE in emergency [4] .…”
Section: Discussionmentioning
confidence: 99%